Limit sugar intake in foods and beverages - Abd. Talib, Ruzita; Mat Jusoh, Hanapi; Buhari, Siti Sabariah; Tan, Yen Nee (Technical Working Group on Nutrition Guidelines For National Coordinating Committee on Food and Nutrition, 2021)
Malaysian Dietary Guidelines (MDGs) are government endorsed documents intended to provide specific recommendations and advice on healthy diets and lifestyles. They are intended to influence consumer food choice based on latest scientific findings on food and nutrient intakes, food supplies, prevalence and public health importance of diet-related health and nutrition outcomes, cultural preferences, and other considerations. It forms the basis for educational programmes and the national food and nutrition policies. The challenge for any dietary guidelines would be to have a coherent policy that take into consideration not only the healthy dietary choices and personal health but also the wider social and environmental impact towards achieving a global environmental sustainability.